Pollen limitation and seed set associated with year-to-year variation in flowering of Gmelina arborea in a natural tropical forest. Issue 2 (4th March 2019) - Khanduri, Vinod Prasad; Kumar, Kewat Sanjay; Sharma, Chandra Mohan; Riyal, Manoj Kumar; Kar, Kalpataru
Abstract: The year-to-year variations in flowering, pollen and fruit production in ten Gmelina arborea individuals in a natural forest were observed over a period of five years, 2009−2013, and pollinator visits were observed closely over two years, 2011 and 2012. A pollen supplementation experiment was also undertaken in two years (2011 and 2012) of contrasting flowering levels. Considerable year-to-year variations were observed in flower, pollen and fruit production. The observed variation represented a normal sequence of good-year and poor-year cycling which is most parsimoniously attributed to resource allocation. The average level of pollen production per individual tree in good flowering years oscillated between 6.6 and 9.62 × 10 8, which in the poor flowering years was between 1.92 and 3.07 × 10 8 . The magnitude of pollen limitation across years was highly significant ( p < 0.0001). Fruit set through supplemental pollination was 73% and 96% greater than that of the open-pollinated branches in the year 2011 and 2012, respectively. Pollen limitation, irrespective of the arrival of outcross pollen, can reduce annual seed set in predominantly bee-pollinated trees. However, various other factors may cause flower abortion in addition to pollen limitation. The results of this study would be very valuable to the seed orchard managers and the silviculturists to manage the seed production areas (SPAs) of G. arborea . The study ultimately recommends supplemental pollination in seed orchards of G. arborea for better genetic gain and good seed yield.